2009
DOI: 10.1007/s10562-008-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

Palladium and Molybdenum Mono and Bimetallic Catalysts on Modernite for Direct NO Decomposition Reaction

Abstract: Palladium and/or molybdenum catalysts supported on mordenite were prepared and characterized by XRD, UV-vis, DRS, textural properties analysis, TPR, TPD and chemical analysis. The Mo-catalyst rapidly deactivated after the first minutes reaction. The Pd-catalysts were active in the NO decomposition reactions. The incorporation of Mo in the Pd-catalysts improved their catalytic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As the most widely studied catalyst, the three-way catalyst with Pt, Pd, and Rh as the active components was found to have high direct NO decomposition activity. [20][21][22] However, most noble metal catalysts show poor resistance to O 2 and a high reaction temperature (600-900 °C), hindering their practical application. 23,24 In contrast, although transition metal oxides and zeolites can function at intermediate temperatures (300-550 °C), 10 their activity is far from the required level, 25 and they are also susceptible to SO 2 poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…As the most widely studied catalyst, the three-way catalyst with Pt, Pd, and Rh as the active components was found to have high direct NO decomposition activity. [20][21][22] However, most noble metal catalysts show poor resistance to O 2 and a high reaction temperature (600-900 °C), hindering their practical application. 23,24 In contrast, although transition metal oxides and zeolites can function at intermediate temperatures (300-550 °C), 10 their activity is far from the required level, 25 and they are also susceptible to SO 2 poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of contaminating the final Pd/C catalyst by Mo can be taken given a report on Mo-Pt/C (claimed to be bimetallic) catalysts that are more active for the targeted transformation than the corresponding Pt/C system [31]. Supported Mo-Pd catalysts have also been applied to other reactions [32][33][34][35][36][37][38][39][40][41][42]. In addition, although in the first paper describing heterogeneous catalysts for glyoxal oxidation, Pt/C catalysts were shown to be more active than Pd/C [43], we have since shown that main-group element-promoted E-Pd/C catalysts (E = Pb, Bi) are more active and selective than monometallic formulations [44][45][46].…”
Section: Introductionmentioning
confidence: 99%